Reformulasi Pengaturan Sanksi Pidana Terhadap Pelaku Kejahatan Seksual Bagi Anak Penyandang Disabilitas - Lubis, Muhammad Al Amien; Erdianto, Erdianto; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Children with disabilities are children who have physical, mental, intellectual or sensorylimitations for a long period of time who, in interacting with their environment and societalattitudes, may encounter obstacles that make it difficult to participate fully and effectively basedon equal rights. Sexual violence against children is regulated in Law Number 35 of 2014concerning Amendments to Law Number 23 of 2002 concerning Child Protection. This rule iscontained in Article 76 D. Article 81 of Law Number 35 of 2014 concerning Child Protectionregulates sanctions for criminal acts of sexual violence (obscene) against children. Althoughthere are regulations governing the protection of children, there is no specific protection forchildren with disabilities. Therefore, if children with disabilities experience sexual violence,they are always at a disadvantage.The objectives to be achieved in this research are firstly to find out the weaknesses ofthe existing criminal sanction arrangements against perpetrators of sexual crimes for childrenwith disabilities in Indonesian positive law and their implementation. The second is to formulatethe ideal punishment to be imposed on perpetrators of sexual crimes for children withdisabilities.The author conducted research using normative juridical methods or literaturestudies in order to obtain secondary data which was divided into 3 (three), namely primary,secondary and tertiary legal materials. In this study, researchers used a statutory approach thatwould examine law, namely the principle of openness which has a relationship to the problemsstudied.From the research results, there are two main things that can be concluded. The firstis related to the weaknesses in the existing criminal sanctions arrangements againstperpetrators of sexual crimes for children with disabilities in Indonesian positive law and how itis currently implemented in Indonesia. The second is the ideal punishment to be imposed onperpetrators of sexual crimes for children with disabilities, because children with disabilitiesare always disadvantaged and there is no special protection for them.The author's suggestion is that the state must update or reformulate laws related tosanctions against sexual crimes against children with disabilities. So that the crime rate ofsexual crimes against children with disabilities in Indonesia can be reduced. Suggesting that theimposition of sanctions on perpetrators of sexual crimes against children with disabilities begiven severe sanctions, namely a minimum of 20 years in prison or in accordance with theweight that should be imposed, namely plus one-third of the maximum sentence and it is hopedthat with this, justice will be achieved, and suggesting that the state should improve educationmore morals and character to all generations of the nation.Keywords : Children-Persons-Disabilities-Sexual-Violence-Reformulation